Extreme right terrorism in the Portuguese transition to democracy: The Portuguese Liberation Army (1974-1976) - Marchi, R. (2022)
This paper offers an in-depth and rigorous analysis of the ELP (Exército de Libertação de Portugal /Portugal Liberation Army), which appears as the most prominent armed organisation of the Portuguese extreme right in the period of transition from authoritarianism to democracy. We address the ELP from its genesis, to its structuring, ideological positioning, identity, strategy and operative capacity, permeability to repression, and dissolution. This study is based on a qualitative methodology which triangulates data dispersed in the existing scientific and journalistic literature with data collected, for the first time, in private archives and through face-to-face interviews with former ELP militants. This paper aims to challenge the idea of the efficiency of the armed extreme-right in the transition period in Portugal, through an in-depth analysis of its most extreme faction.